Feasibility in the implementation of 4.0 technologies in the intralogistic activities of Logistic Operators of the Department of Atlántico, a look towards the organizational efficiency (2020)
The intralogistic activities of the logistics operators are defined in the grouping of all the processes linked to the reception, storage and distribution of raw materials and final products. Therefore, the study of intralogistic processes as an activity is part of the value chain of a company and, through its management, the result of the operation and an adequate level of customer service will depend on it. The project proposes to evaluate the feasibility of the use of technologies of the industry 4.0 in the intralogistic activities that allow the integration of processes of automation and control for the continuous improvement of the decision making in the processes of storage, load and unload of the logistic operators of the department of the Atlantic - Colombia for the improvement of the enterprise efficiency. Therefore, a review of the literature is carried out framed in three categories: intralogistics, Industry and Technology 4.0, and the application of an instrument to measure the absorption of technologies 4.0 in the company under study, which was validated as a result the importance of Simulation, Automation and load sensing, Collaborative Robotics, Big Data powered by M2M (Machine to Machine communication) and Predictive maintenance - predictive analysis and M2M communication as a solution to the needs that are represented in the environment of the Logistics Operators of the Department of Atlántico -Colombia, based on the challenges and projections imposed by the dynamics of the international market and especially thefree trade agreements that the New Granada nation has signed and framed in recent years with the intention of making itseconomy and especially the organizations of its different regions more efficient.